Effects of doping, morphology and film-thickness of photo-anode materials for dye sensitized solar cell application – A review. (July 2016) - Sengupta, D.; Das, P.; Mondal, B.; Mukherjee, K.
Abstract: Dye sensitized solar cells are attractive as simple and low cost renewable energy source. In dye sensitized solar cells, photo-anode plays significant role for collection and transportation of photo-excited electrons from dye to external electric circuit. Usually, wide band gap semiconducting metal oxides like titania, zinc oxide etc are deposited over transparent conducting substrate to prepare the photo-anodes. The performances of the photo-anodes depend on the band gap, morphology, composition of metal oxides and thickness of metal oxide layers. Enormous research efforts have been accomplished for studying the photo-voltaic characteristics of the dye sensitized solar cells by varying the aforementioned influencing parameters. However, the research activities executed towards the modification of photo-anode for dye sensitized solar cell application are quite scattered. It seems therefore important to summarize the research efforts executed towards the development of photo-anode for dye sensitized solar cell. In the present review, the effect of influencing parameters on the photo-voltaic characteristics of photo-anode for dye sensitized solar cell application is discussed. The descriptions have been made by summarizing the relevant literature reports. Graphical abstract: